A disequilibrium evaluation of public intervention in agricultural credit markets. Issue 1 (2nd May 2017) - Hubbs, Todd; Kuethe, Todd
Abstract : Purpose: Agricultural producers rely on debt capital to support many functions of their enterprise, yet private credit markets are frequently characterized by an imbalance between supply and demand. As a result, a number of public lending programs exist to mitigate the perceived market failures of private credit markets that serve agricultural producers. The paper aims to discuss these issues. Design/methodology/approach: This study uses a structural disequilibrium model to examine the potential for excess demand or supply in the private market for non-real estate farm loans between 1978 and 2014. Findings: The model demonstrates that the market is frequently characterized by disequilibrium, fluctuating between periods of excess demand and excess supply. These disequilibrium periods motivate the discussion of public intervention as a policy proposal within the agricultural sector. Originality/value: This study uses traditional disequilibrium modeling to evaluate the private credit market for agriculture lending in a manner that has not been attempted previously in the literature. The model uses maximum likelihood methods with non-linear solution algorithms to investigate excess supply and demand in the sector.